Raising public awareness an infographic on occupational therapy as an aid in optimal mental health and welfare in Davao City - Buenaobra, Andrea Trisha A. (2023)
The results in the formative evaluation of this research study revealed that there is a lack of public awareness of Occupational Therapy in the mental health setting in Davao City. With this being stated, this study aimed to introduce and raise awareness of Occupational Therapy as an aid in optimal mental health and welfare in Davao City through communication material. The development of the communication material was guided by the Health Communication Program Cycle and the Elaboration Likelihood Model Theory in crafting messages and identifying the material which was targeted to the audience of the study In achieving this, the researcher conducted formative research and analysis from key-informant interviews of healthcare workers and survey on the residents of Davao City to explore the respondents? socio-demographics, level of awareness on mental health and occupational therapy, and the respondents? knowledge index on the concepts to curate the appropriate communication material. The result of the study led to the development of an infographic as an effective information and communication (EIC) tool to raise awareness of occupational therapy as an aid in optimal mental health and welfare in Davao City
Thesis (BA Communication and Media Arts) --University of the Philippines Mindanao, 2023